Copper paste and preparation method and application thereof

By using the copper pulp formula composed of copper powder and copper powder, the existing copper pulp has the problem of bubbling and poor acid resistance after sintering.

CN119361209APending Publication Date: 2025-01-24德阳三环科技有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411483704.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing copper slurry is prone to appearance bubbles and poor acid resistance after sintering, which affects the reliability and service life of the product.

Method used

Copper milk formula containing copper -containing materials, glass powder, adhesives, tactiles and solvents. Among them, copper -containing materials are composed of copper -covered powder and copper powder, and copper powder is covered with nuclear shell structure. Layer, contains oxide, prepare copper pulp through specific preparation methods and process processes.

Benefits of technology

It improves the density and reliability of the terminal electrode, reduces the proportion of edge cracking and glass overflow, and enhances the conductive performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098170490000081
    Figure BDA0005098170490000081
  • Figure BDA0005098170490000091
    Figure BDA0005098170490000091
  • Figure BDA0005098170490000092
    Figure BDA0005098170490000092
Patent Text Reader

Abstract

The invention belongs to the field of conductive materials, and particularly discloses copper paste and a preparation method and application thereof.The copper paste comprises, by mass, 55-77.5% of a copper-containing material, 7-14% of glass powder, 5-10% of a binder, 0.5-3% of a thixotropic agent and 10-18% of a solvent; the copper-containing material comprises, by mass, 5%-20% of coated copper powder and 80%-95% of copper powder. When the copper paste disclosed by the invention is applied to the terminal electrode of the chip multilayer ceramic capacitor, the terminal electrode can simultaneously have the following properties of relatively low edge cracking ratio, relatively high compactness, relatively low glass overflow ratio, relatively high reliability and excellent conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electronic paste, and in particular relates to a copper paste and a preparation method and application thereof. Background Art

[0002] Electronic paste is a functional material widely used in the preparation of many electronic components. It can form a conductive layer on carriers such as ceramics and glass through printing, leveling, sintering and other processes, and is further used in various electronic equipment products such as integrated circuits, resistors, capacitors, etc.

[0003] Electronic paste is generally composed of metal phase functional powder and organic phase carrier. According to the different types of metals contained, it can be divided into gold paste, silver paste, copper paste, nickel paste, etc. Among them, silver paste has excellent conductivity and is often widely used in the preparation of external electrodes of multi-layer ceramic capacitors (MLCC). However, silver paste is expensive and has a high preparation cost. In the actual production process, it has gradually been replaced by copper paste with low price and good conductivity.

[0004] At present, the most commonly used MLCC external electrode is a three-layer structure, which includes a copper layer, a nickel layer, and a tin layer. The copper layer, as the innermost electrode that leads the inner electrode and is directly connected to the nickel layer, plays a decisive role in the reliability of the MLCC. The prior art uses copper slurry to obtain the copper layer by immersion and sintering, while the nickel layer and the tin layer are obtained by electroplating. The copper layer prepared by the copper terminal method will have blistering appearance after sintering and poor acid resistance, which will affect the reliability and service life of the product. Summary of the invention

[0005] In order to overcome the problems existing in the prior art, one of the objectives of the present invention is to provide a copper paste.

[0006] A second object of the present invention is to provide a method for preparing copper slurry.

[0007] A third object of the present invention is to provide a chip-type multilayer ceramic capacitor.

[0008] A fourth object of the present invention is to provide application of the copper paste in the field of electronic devices.

[0009] In order to achieve the above object, the technical solution adopted by the present invention is:

[0010] The first aspect of the present invention provides a copper paste, comprising the following components in mass percentage: 55-77.5% copper-containing material, 7-14% glass powder, 5-10% binder, 0.5-3% thixotropic agent, and 10-18% solvent;

[0011] The copper-containing material comprises 5-20% by mass of coated copper powder and 80-95% by mass of copper powder; the coated copper powder is a core-shell structure; the core of the coated copper powder is copper; the outer shell of the coated copper powder is a metal oxide layer; the metal oxide layer contains tin oxide;

[0012] Taking the total mass percentage of the metal oxide layer as 100%, the mass percentage of tin oxide is 65-100%.

[0013] In the copper paste of the present invention, the mass percentage of the copper-containing material is 55-77.5%, for example, it can be selected from 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 77.5%; preferably, the mass percentage of the copper-containing material is 63.5-70%.

[0014] In the copper paste of the present invention, the mass percentage of glass powder is 7-14%, for example, it can be selected from 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%; preferably, the mass percentage of glass powder is 8-12%; further preferably, the mass percentage of glass powder is 9-11%.

[0015] In the copper paste of the present invention, the mass percentage of the binder is 5-10%, for example, it can be selected from 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%; preferably, the mass percentage of the binder is 6-9%; further preferably, the mass percentage of the binder is 7-8%.

[0016] In the copper paste of the present invention, the mass percentage of the thixotropic agent is 0.5-3%, for example, it can be selected from 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%. Preferably, the mass percentage of the thixotropic agent is 0.8-2.5%; more preferably, the mass percentage of the thixotropic agent is 1-2%.

[0017] In the copper paste of the present invention, the mass percentage of the solvent is 10-18%, for example, it can be selected from 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%; preferably, the mass percentage of the solvent is 12-16%; further preferably, the mass percentage of the solvent is 13-15%.

[0018] In the copper-containing material of the present invention, the mass percentage of the coated copper powder is 5-20%, for example, it can be selected from 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%; preferably, the mass percentage of the coated copper powder is 8-16%; further preferably, the mass percentage of the coated copper powder is 10-14%. When the amount of the coated copper powder added is less than 5%, it cannot play a role in inhibiting the shrinkage of the copper powder, which will cause cracking of the edges of the product; when the amount of the coated copper powder added is greater than 20%, the density is too poor, which will reduce the reliability of the product.

[0019] In the copper-containing material of the present invention, the mass percentage of copper powder is 80-95%, for example, can be selected from 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%.

[0020] The mass percentage of tin oxide in the metal oxide layer of the present invention is 65-100%, for example, it can be selected from 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%. When the mass percentage of tin oxide in the metal oxide layer is 65-100%, the shrinkage of the copper-containing material can be suppressed, the risk of glass powder overflow can be reduced, and the problem of cracking of the edge of the product can be solved.

[0021] Preferably, the metal oxide layer further contains at least one of silver oxide and nickel oxide.

[0022] Preferably, the copper powder is copper flakes with an aspect ratio of 2 to 10, for example, selected from 2, 3, 4, 5, 6, 7, 8, 9, and 10.

[0023] Preferably, the average particle size of the coated copper powder is 1 to 3 μm, for example, it can be selected from 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3 μm. When the particle size of the coated copper powder is less than 1 μm, the sintering temperature is too high, which may easily cause cracking of the edges of the product. When the particle size of the coated copper powder is greater than 3 μm, the copper slurry will be difficult to sinter, and the density of the copper electrode will deteriorate.

[0024] Preferably, the average particle size of the copper powder is 2 to 4 μm, for example, 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm, 3.8 μm, 3.9 μm, 4 μm. When the particle size of the copper powder is less than 2 μm, the sintering temperature will be too high, which may easily cause the edge of the product to crack. When the particle size of the copper powder is greater than 4 μm, the copper slurry will be difficult to sinter, and the density of the copper electrode will deteriorate.

[0025] Preferably, the thickness of the metal oxide layer is 50-200 nm, for example, can be selected from: 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm. When the thickness of the metal oxide layer is less than 50 nm, the thickness is too small to inhibit sintering shrinkage, and when the thickness of the metal oxide layer is greater than 200 nm, the thickness is too large and the sintering density is too poor.

[0026] Preferably, the binder is selected from at least one of ethyl cellulose, acrylic resin, epoxy resin, nitrocellulose resin, styrene resin, phenolic resin, modified ethyl cellulose resin, and modified acrylic resin; further preferably, the binder is selected from at least one of ethyl cellulose, acrylic resin, epoxy resin, nitrocellulose resin, styrene resin, and phenolic resin.

[0027] Preferably, the solvent is selected from at least one of terpineol, hydrogenated terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, and dipropylene glycol propyl ether.

[0028] Preferably, the thixotropic agent is selected from at least one of hydrogenated castor oil, polyamide wax and fumed silica.

[0029] Preferably, the copper paste comprises the following components in mass percentage: 63.5-70% copper-containing material, 8-12% glass powder, 6-9% binder, 1-2% thixotropic agent, and 13-15% solvent; further preferably, the copper paste comprises the following components in mass percentage: 64%-70% copper-containing material, 9-11% glass powder, 7-8% binder, 1-2% thixotropic agent, and 13-15% solvent.

[0030] Preferably, the copper-containing material comprises 8-16% by mass of coated copper powder and 84-92% by mass of copper powder; further preferably, the copper-containing material comprises 10-14% by mass of coated copper powder and 86-90% by mass of copper powder.

[0031] Preferably, the glass powder comprises the following components in mass percentage: 40-70% BaO, 5-15% Al 2 O 3 10~30%B 2 O 3 、3~10%SiO 2 , 3~8%CaO, 1~5%TiO 2 , 0~3%Na 2 O, 0-3% SrO.

[0032] In the glass powder of the present invention, the mass percentage of BaO is 40-70%, for example, can be selected from 40%, 45%, 50%, 55%, 60%, 65%, 70%.

[0033] In the glass powder of the present invention, Al 2 O 3 The mass percentage is 5-15%, for example, can be selected from 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%.

[0034] In the glass powder of the present invention, B 2 O 3 The mass percentage is 10-30%, for example, can be selected from 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%.

[0035] In the glass powder of the present invention, SiO 2 The mass percentage is 3-10%, for example, can be selected from 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.

[0036] In the glass powder of the present invention, the mass percentage of CaO is 3-8%, for example, can be selected from 3%, 4%, 5%, 6%, 7%, 8%.

[0037] In the glass powder of the present invention, TiO 2 The mass percentage is 1-5%, for example, can be selected from 1%, 2%, 3%, 4%, 5%.

[0038] In the glass powder of the present invention, Na 2The mass percentage of O is 0-3%, for example, can be selected from 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%.

[0039] In the glass powder of the present invention, the mass percentage of SrO is 0-3%, for example, can be selected from 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%.

[0040] Preferably, when the metal oxide layer is tin oxide, the coated copper powder is prepared by a preparation method comprising the following steps: copper powder, stannous salt and an organic solvent are mixed, and then subjected to a hydrolysis reaction with water to obtain the coated copper powder.

[0041] Preferably, when the metal oxide layer is a mixture of tin oxide and nickel oxide, the coated copper powder is prepared by a preparation method comprising the following steps:

[0042] A1: copper powder, stannous salt and organic solvent are mixed, and then hydrolyzed with water to obtain tin oxide coated copper powder;

[0043] A2: The tin oxide coated copper powder, nickel salt and hydrazine are reacted in an alkaline environment to obtain the product.

[0044] Preferably, when the metal oxide layer is a mixture of tin oxide and silver oxide, the coated copper powder is prepared by a preparation method comprising the following steps:

[0045] B1: copper powder, stannous salt and organic solvent are mixed, and then hydrolyzed with water to obtain tin oxide coated copper powder;

[0046] B2: heating the tin oxide coated copper powder, hydrazine hydrate and alkali to react to obtain treated tin oxide coated copper powder;

[0047] B3: The treated tin oxide coated copper powder is subjected to chemical silver plating, then reacted with vitamin C, and then reacted with acid and a silane coupling agent to obtain the product.

[0048] Preferably, in the above three methods for preparing coated copper powder, the copper powder needs to be washed with a cleaning agent before use.

[0049] Preferably, the detergent comprises the following components in mass concentrations: 10-50 g / L HCl, 20-80 g / L sulfuric acid, 5-15 g / L tripolyphosphate, and 5-40 g / L citrate.

[0050] Preferably, the stannous salt is selected from stannous octoate or stannous fluoride.

[0051] Preferably, the mass ratio of the copper powder to the stannous salt is (0.25-0.75):1.

[0052] Preferably, the organic solvent comprises isopropanol.

[0053] Preferably, in the mixed solution of copper powder, stannous salt and organic solvent, the concentration of copper powder is 0.05-0.5 g / mL.

[0054] Preferably, the volume of the water is 0.2% to 1% of the total volume of the copper powder, the stannous salt and the organic solvent.

[0055] Preferably, the hydrolysis reaction time is 12 to 24 hours.

[0056] Preferably, the step A2 is: preparing the tin oxide coated copper powder and nickel salt into a mixed solution; and then reacting with hydrazine in an alkaline environment to obtain.

[0057] Preferably, in the mixed solution, the concentration of nickel salt is 35-45 g / L.

[0058] Preferably, the reaction temperature in step A2 is 80-90°C.

[0059] Preferably, the alkaline environment has a pH of 11.5 to 13.5.

[0060] Preferably, the components of the silver plating solution during the chemical silver plating include silver salt and ethylenediamine.

[0061] Preferably, the acid is acetic acid and / or formic acid.

[0062] The second aspect of the present invention provides a method for preparing the copper slurry according to the first aspect of the present invention, comprising the following steps:

[0063] The raw materials are mixed and then rolled to obtain the copper slurry.

[0064] Preferably, the step of mixing the raw materials comprises the following steps:

[0065] The solvent and the binder are heated and mixed to obtain glue;

[0066] mixing glass powder, coated copper powder and copper powder to obtain an inorganic phase;

[0067] The glue and the inorganic phase are mixed.

[0068] Preferably, the heating and mixing temperature is 80-90°C. For example, the heating temperature can be selected from 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, and 90°C.

[0069] Preferably, the stirring frequency of the heated mixing is 10 to 20 Hz, for example, can be selected from 10 Hz, 11 Hz, 12 Hz, 13 Hz, 14 Hz, 15 Hz, 16 Hz, 17 Hz, 18 Hz, 19 Hz, and 20 Hz.

[0070] Preferably, the mixing time in the preparation step of the inorganic phase is 10 to 30 min, for example, can be selected from 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min, and 30 min.

[0071] Preferably, the stirring rate in the preparation step of the inorganic phase is 100-200 r / min, for example, can be selected from 100 r / min, 110 r / min, 120 r / min, 130 r / min, 140 r / min, 150 r / min, 160 r / min, 170 r / min, 180 r / min, 190 r / min, 200 r / min.

[0072] Preferably, the mixing time in the step of mixing the glue and the inorganic phase is 30 to 90 min, for example, can be selected from 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min.

[0073] Preferably, the stirring rate in the step of mixing the glue and the inorganic phase is 300-600 r / min, for example, can be selected from 300 r / min, 350 r / min, 400 r / min, 450 r / min, 500 r / min, 550 r / min, 600 r / min.

[0074] Preferably, the gap between the rolling mill rollers is 50-500 μm, for example, can be selected from 50 μm, 80 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, 500 μm.

[0075] Preferably, the frequency of the rolling mill rollers is 20-60 r / min, for example, can be selected from 20 r / min, 30 r / min, 40 r / min, 50 r / min, 60 r / min.

[0076] Preferably, the rolling times are 4 to 8 times, for example, can be selected from 4 times, 5 times, 6 times, 7 times, and 8 times.

[0077] The third aspect of the present invention provides a chip-type multilayer ceramic capacitor, including a terminal electrode; the terminal electrode is made of the copper paste described in the first aspect of the present invention.

[0078] The fourth aspect of the present invention provides the use of the copper paste described in the first aspect of the present invention in the field of electronic devices.

[0079] Preferably, the electronic device comprises an integrated circuit, a resistor device or a capacitor.

[0080] The beneficial effect of the present invention is that when the copper paste of the present invention is applied to the terminal electrode of the chip-type multilayer ceramic capacitor, the terminal electrode can have the following properties at the same time: a lower edge cracking ratio, a higher density, a lower glass overflow ratio, a higher reliability and excellent conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0081] Figure 1 1 is a flow chart of the preparation process of copper slurry in an embodiment of the present invention.

[0082] Figure 2 1 is a flow chart of the process for preparing the terminal electrodes of a chip-type multilayer ceramic capacitor in an embodiment of the present invention. DETAILED DESCRIPTION

[0083] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.

[0084] The raw material information used in the examples and comparative examples of the present invention is as follows:

[0085] The copper powder is copper flakes with an aspect ratio of 3 to 6;

[0086] The binder is ethyl cellulose;

[0087] The thixotropic agent is polyamide wax;

[0088] The solvent is terpineol.

[0089] Example 1

[0090] This example provides a copper paste, which is composed of the following components in mass percentage: 64% copper-containing material, 11% glass powder, 8% adhesive, 15% solvent, and 2% thixotropic agent. Among them, the copper-containing material is composed of coated copper powder and copper powder; taking the total mass percentage of the copper-containing material as 100%, the mass percentage of the coated copper powder is 5%, the mass percentage of the copper powder is 95%, and the particle size of the copper powder is 3μm, as shown in Table 1 below (wherein, the contents in Table 1 are all mass percentages, and the contents of the coated copper powder and the copper powder are all calculated based on the total mass percentage of the copper-containing material as 100%). The particle size of the coated copper powder is 3μm, and the number of the coated copper powder is B4. The coated copper powder is a layer of metal oxide layer coated on the surface of the copper powder. The material of the metal oxide layer is tin oxide, and the thickness of the metal oxide layer is 130 to 150nm, as shown in Table 2 below. The number of the glass powder is G1, and the glass powder is composed of the following components in mass percentage: BaO 40%, Al 2 O 3 10%, B 2 O 3 30%, SiO 2 10%, CaO 5%, TiO 2 5%, as shown in the following Table 3.

[0091] Embodiments 2 to 6

[0092] The copper pastes in Examples 2 to 6 are different from Example 1 only in that the contents of the coated copper powder and the copper powder are different. The formulas of the copper pastes in Examples 2 to 6 are shown in Table 1, the formula of the coated copper powder is shown in Table 2, and the formula of the glass powder is shown in Table 3.

[0093] Example 7

[0094] This example provides a copper paste, which differs from Example 1 in that the contents of coated copper powder and copper powder are different. This example is composed of the following components in mass percentage: 64% copper-containing material, 11% glass powder, 8% adhesive, 15% solvent, and 2% thixotropic agent. Among them, the copper-containing material is composed of coated copper powder and copper powder; taking the total mass percentage of the copper-containing material as 100%, the mass percentage of the coated copper powder is 12%, the mass percentage of the copper powder is 88%, and the particle size of the copper powder is 3μm, as shown in Table 1. The particle size of the coated copper powder is 3μm, and the coated copper powder is numbered B4. The coated copper powder is a layer of metal oxide layer coated on the surface of the copper powder. The material of the metal oxide layer is tin oxide, and the thickness of the metal oxide layer is 130-150nm, as shown in Table 2. The number of the glass powder is G1, and the glass powder is composed of the following components in mass percentage: BaO 40%, Al 2 O 3 10%, B 2 O 3 30%, SiO2 10%, CaO 5%, TiO 2 5%, as shown in Table 3.

[0095] Embodiments 8 to 9

[0096] The copper paste in Examples 8 to 9 is different from that in Example 7 only in that the particle size of the copper powder is different. The formula of the copper paste in Examples 8 to 9 is shown in Table 1, the formula of the coated copper powder is shown in Table 2, and the formula of the glass powder is shown in Table 3.

[0097] Embodiments 10 to 20

[0098] The copper pastes of Examples 10 to 20 differ from Example 7 only in that the types (i.e., numbers) of the coated copper powders are different, wherein the thickness of the tin oxide metal oxide layer in the coated copper powders is adjusted in Examples 10 to 14, and the particle size of the coated copper powders is adjusted in Examples 15 to 16; and the composition of the metal oxide layer in the coated copper powders is adjusted in Examples 17 to 20. The formula of the copper pastes in Examples 10 to 20 is shown in Table 1, the formula of the coated copper powder is shown in Table 2, and the formula of the glass powder is shown in Table 3.

[0099] Examples 21-22

[0100] The copper paste of Examples 21-22 is different from that of Example 7 only in that the amounts of glass powder, binder, solvent and thixotropic agent are different, and the formula (i.e., number) of the glass powder is also different. The formula of the copper paste in Examples 21-22 is shown in Table 1, the formula of the coated copper powder is shown in Table 2, and the formula of the glass powder is shown in Table 3.

[0101] Comparative Examples 1-2

[0102] The copper paste in Comparative Examples 1-2 is different from Example 7 only in that the amount of coated copper powder and copper powder is different. The formula of the copper paste in Comparative Examples 1-2 is shown in Table 1, the formula of the coated copper powder is shown in Table 2, and the formula of the glass powder is shown in Table 3.

[0103] Comparative Example 3

[0104] The copper paste in Comparative Example 3 is different from that in Example 7 only in that the type of coated copper powder is different and the particle size of the copper powder is different. The formula of the copper paste in Comparative Example 3 is shown in Table 1, the formula of the coated copper powder is shown in Table 2, and the formula of the glass powder is shown in Table 3.

[0105] Comparative Examples 4 to 11

[0106] The copper pastes in Comparative Examples 4 to 11 are different from those in Example 7 only in that the types of coated copper powders are different. The formulas of the copper pastes in Comparative Examples 4 to 11 are shown in Table 1, the formulas of the coated copper powders are shown in Table 2, and the formulas of the glass powders are shown in Table 3.

[0107] Table 1 Formulas of copper pastes in Examples 1 to 22 and Comparative Examples 1 to 11

[0108]

[0109]

[0110] Table 2 Formulas of coated copper powders with different numbers

[0111]

[0112] Table 3 Formulas of glass powders with different numbers

[0113]

[0114] Reference Figure 1 The copper pastes in Examples 1 to 22 and Comparative Examples 1 to 11 of the present invention are all prepared by the following preparation method, and the specific steps include:

[0115] (1) Preparation of glue: Add a formulated amount of solvent into a stirring tank and heat it at a constant temperature of 90° C. Then slowly add a formulated amount of adhesive into the stirring tank (stirring frequency: 20 Hz) until the adhesive is completely dissolved to obtain glue;

[0116] (2) Inorganic phase mixing: Add the formulated amount of glass powder, coated copper powder and copper powder into a mixing tank and stir until uniform, stirring time 30 minutes, stirring speed 200r / min;

[0117] (3) Preliminary mixing: Add the glue into the mixing cylinder containing the inorganic phase and stir to allow the glue to preliminarily wet the inorganic phase until no dry powder is present (add the formulated amount of thixotropic agent during the stirring process). Stirring time: 60 min, stirring speed: 500 r / min, to obtain a dispersed slurry.

[0118] (4) Rolling of slurry: Use a three-roll mill to fully mix the dispersed slurry. By controlling the gap between the rollers and the frequency of the rollers, the gap is 300 μm, the frequency is 40 r / min, and the number of rolling times is 8 times, a copper slurry with uniform dispersion and roughness within the qualified range is prepared, and the particle size of the copper slurry is less than 1.5 μm.

[0119] The preparation method of the coated copper powder used in Examples 1 to 22 and Comparative Examples 1 to 11 of the present invention is as follows:

[0120] 1. Coated copper powder containing tin oxide metal oxide layer

[0121] Examples 1 to 16, Examples 21 to 22, and Comparative Examples 1 to 6 all use a tin oxide metal oxide layer to coat copper powder, and the tin oxide coated copper powder is prepared by the following preparation method:

[0122] (1) Cleaning the copper powder: Clean the copper powder with a cleaning solution and then dry it in a vacuum (cleaning solution composition: 10-50 g / L HCl, 20-80 g / L sulfuric acid, 5-15 g / L tripolyphosphate, 5-40 g / L citrate);

[0123] (2) preparing a solution: adding the cleaned copper powder to an isopropanol solvent to obtain a copper solution having a concentration of 0.3 g / mL;

[0124] (3) Adding stannous salt or stannous salt solution: adding stannous salt or its solution (the solvent is isopropanol) to the copper powder solution to form a mixed solution. The stannous salt can be stannous octoate or stannous fluoride. By adjusting the mass ratio of stannous salt to copper powder, the thickness of the tin oxide metal oxide layer can be adjusted. For example, when a tin oxide layer with a thickness of 50 to 80 nm needs to be prepared, the mass ratio of copper powder to stannous salt can be adjusted to (0.7 to 0.75):1; when a tin oxide layer with a thickness of 80 to 100 nm needs to be prepared, the mass ratio of copper powder to stannous salt can be adjusted to (0.65 to 0.7):1; when a tin oxide layer with a thickness of 130 to 150 nm needs to be prepared, the mass ratio of copper powder to stannous salt can be adjusted to (0.5 to 1.0):1. The mass ratio of copper powder and stannous salt is adjusted to (0.6-0.62):1; when a tin oxide layer with a thickness of 150-180 nm needs to be prepared, the mass ratio of copper powder and stannous salt can be adjusted to (0.5-0.6):1; when a tin oxide layer with a thickness of 180-200 nm needs to be prepared, the mass ratio of copper powder and stannous salt can be adjusted to (0.25-0.5):1; when a tin oxide layer with a thickness of 20-30 nm needs to be prepared, the mass ratio of copper powder and stannous salt can be adjusted to (0.8-0.85):1, and when a tin oxide layer with a thickness of 300-350 nm needs to be prepared, the mass ratio of copper powder and stannous salt can be adjusted to (0.2-0.22):1;

[0125] (4) Hydrolysis reaction: Deionized water is added during the stirring process. A syringe pump or a pipette can be used. The volume of the added deionized water accounts for 0.2% to 1% of the volume of the above mixed solution. The reaction is stirred and continued at room temperature for 24 hours to form tin oxide-coated copper powder.

[0126] 2. Coated copper powder containing a composite metal oxide layer of tin oxide and nickel oxide

[0127] Example 17, Example 19 and Comparative Example 8 all use copper powder coated with a composite metal oxide layer containing tin oxide and nickel oxide. The specific preparation method of the coated copper powder is:

[0128] The first step is to prepare tin oxide coated copper powder particles:

[0129] (1) Cleaning the copper powder: Clean the copper powder with a cleaning solution and then dry it in a vacuum (cleaning solution composition: 10-50 g / L HCl, 20-80 g / L sulfuric acid, 5-15 g / L tripolyphosphate, 5-40 g / L citrate);

[0130] (2) Preparing a solution: adding copper powder to an isopropanol solvent to obtain a copper solution, wherein the concentration of the copper solution in Example 17 is 0.5 g / mL; the concentration of the copper solution in Example 19 is 0.3 g / mL; and the concentration of the copper solution in Comparative Example 8 is 0.2 g / mL;

[0131] (3) adding stannous salt or stannous salt solution: adding stannous salt or its solution (solvent is isopropanol) to the copper powder solution to form a mixed solution, the stannous salt can be stannous octoate or stannous fluoride, and the mass ratio of stannous salt to copper powder is 1:4;

[0132] (4) Hydrolysis reaction: Deionized water is added during the stirring process. A syringe pump or a pipette can be used. The volume of deionized water added is 0.2% to 1% of the volume of the mixed solution. The reaction is continued at room temperature for 24 hours to form tin oxide-coated copper powder.

[0133] The second step is to prepare tin oxide and nickel oxide coated copper powder particles:

[0134] First, prepare a 40g / L nickel sulfate solution, heat it to 85°C, add 50g of the above-mentioned tin oxide-coated copper powder under stirring, adjust the solution pH to 11.5-13.5, slowly add 80mL of hydrazine per liter of nickel sulfate solution under stirring, react until completion, filter and wash, and vacuum dry at 70°C to obtain a coated copper powder containing a composite metal oxide layer of tin oxide and nickel oxide.

[0135] 3. Coated copper powder containing a composite metal oxide layer of tin oxide and silver oxide

[0136] In Example 18, Example 20 and Comparative Example 9, a copper powder coated with a composite metal oxide layer containing tin oxide and silver oxide is used. The specific preparation method of the coated copper powder is as follows:

[0137] The first step is to prepare tin oxide coated copper powder particles:

[0138] (1) Cleaning the copper powder: Clean the copper powder with a cleaning solution and then dry it in a vacuum (cleaning solution composition: 10-50 g / L HCl, 20-80 g / L sulfuric acid, 5-15 g / L tripolyphosphate, 5-40 g / L citrate);

[0139] (2) preparing a solution: adding copper powder to an isopropanol solvent to obtain a copper solution, wherein the concentration of the copper solution in Example 18 is 0.5 g / mL; the concentration of the copper solution in Example 20 is 0.3 g / mL; and the concentration of the copper solution in Comparative Example 9 is 0.2 g / mL;

[0140] (3) Adding stannous salt or stannous salt solution: adding stannous salt or its solution (solvent isopropanol) to the copper powder solution to form a mixed solution, wherein the stannous salt may be stannous octoate or stannous fluoride, and the mass ratio of the stannous salt to the copper powder in Example 18 is 1:4; the mass ratio of the stannous salt to the copper powder in Example 20 is 1:2; the mass ratio of the stannous salt to the copper powder in Comparative Example 9 is 1:4;

[0141] (4) Hydrolysis reaction: deionized water is added during the stirring process. A syringe pump or a pipette can be used. The volume of deionized water added is 0.2% to 1% of the volume of the mixed solution. The reaction is continued at room temperature with stirring for 24 hours to form tin oxide-coated copper powder.

[0142] The second step is to prepare tin oxide and silver oxide coated copper powder particles:

[0143] Take 100g of the above-mentioned tin oxide-coated copper powder, ultrasonically disperse it in 5L of aqueous solvent, add 50g of sodium hydroxide and 50mL of hydrazine hydrate, and treat it at 60°C for 2 hours. After filtering and washing, the copper powder is ultrasonically dispersed in 5L of aqueous solvent for chemical silver plating. The components of the chemical silver plating solution are: 300mL of water, 25g of silver nitrate and 35mL of ethylenediamine. The chemical silver plating solution is slowly added dropwise to the copper powder-containing liquid after the above treatment. After the addition is completed, react for 1 hour, then add 50mL of a 0.5mol / L vitamin C aqueous solution, and continue to react for 30 minutes to obtain a silver-coated copper powder crude product. After filtering, secondary coating is performed. The components of the chemical silver plating solution are: 150mL of water, 12g of silver nitrate and 18mL of ethylenediamine. The chemical silver plating solution is gradually added dropwise to the silver-coated copper powder crude product. After the addition is completed, react for 1 hour, then add 50mL of a 0.2mol / L vitamin C aqueous solution, and continue to react for 30 minutes. After filtering, the mixture was repeatedly rinsed with clean water, and then dispersed in an ethanol solution containing formic acid, acetic acid and silane coupling agent KH-550, ultrasonically stirred for 1 hour, filtered again, and dried at 90°C for 5 hours to obtain a coated copper powder containing a composite metal oxide layer of tin oxide and silver oxide.

[0144] 4. Coated copper powder containing nickel oxide metal oxide layer

[0145] Comparative Example 10 uses a coated copper powder containing a nickel oxide metal oxide layer, and its preparation method is as follows:

[0146] First, prepare a 40g / L nickel sulfate solution, heat it to 85°C, add 50g of copper powder under stirring, adjust the solution pH to 11.5-13.5, slowly add 80mL of hydrazine per liter of nickel sulfate solution under stirring, react until completion, filter and wash, and vacuum dry at 60-80°C to obtain a coated copper powder containing a nickel oxide metal oxide layer.

[0147] 5. Coated copper powder containing silver oxide metal oxide layer

[0148] Comparative Example 11 uses silver oxide coated copper powder, and its preparation method is as follows:

[0149] Take 100g of copper powder, ultrasonically disperse it in 5L of aqueous solvent, add 50g of sodium hydroxide and 50mL of hydrazine hydrate, and treat it at 60°C for 2 hours. After filtering and washing, the copper powder is ultrasonically dispersed in 5L of aqueous solvent for chemical silver plating. The components of the chemical silver plating solution are: 300mL of water, 25g of silver nitrate and 35mL of ethylenediamine. The chemical silver plating solution is slowly added dropwise to the copper powder-containing liquid after the above treatment. After the addition is completed, react for 1 hour, then add 50mL of a 0.5mol / L vitamin C aqueous solution, and continue to react for 30 minutes to obtain a silver-coated copper powder crude product. After filtering, secondary coating is performed. The components of the chemical silver plating solution are: 150mL of water, 12g of silver nitrate and 18mL of ethylenediamine. The chemical silver plating solution is gradually added dropwise to the silver-coated copper powder crude product. After the addition is completed, react for 1 hour, then add 50mL of a 0.2mol / L vitamin C aqueous solution, and continue to react for 30 minutes. After filtering, the product was repeatedly rinsed with clean water, and then dispersed in an ethanol solution containing formic acid, acetic acid and silane coupling agent KH-550, ultrasonically stirred for 1 hour, filtered again, and dried at 90°C for 5 hours to obtain a silver oxide-coated copper powder product.

[0150] The copper pastes in Examples 1 to 22 and Comparative Examples 1 to 11 can be used to prepare terminal electrodes of chip-type multilayer ceramic capacitors.

[0151] Reference Figure 2 The preparation process flow chart in the embodiment 1 to 22 and the comparative examples 1 to 11 are respectively prepared into the outer electrodes of the chip-type multilayer ceramic capacitor, and the specific preparation method is as follows:

[0152] (1) Place the capacitor chip flatly into the rubber tray and place it at the termination station;

[0153] (2) The copper slurry is evenly spread on the copper plates of station one and station two, and the slurry thickness and copper dipping parameters (including copper dipping film thickness, copper dipping descending speed, copper dipping recovery speed, copper dipping residence time, etc.) are set by adjusting the control panel;

[0154] (3) The first side and the second side are treated with end caps respectively. After each end cap is treated, it is necessary to dry it before proceeding to the next step. The drying time is 20 minutes and the drying temperature is 150°C.

[0155] (4) After the termination treatment on both sides is completed, the material can be unloaded and the terminal electrode sintering treatment is carried out. The sintering temperature is 820°C, the time is 10 minutes, and the sintering atmosphere is a mixture of nitrogen, hydrogen, water vapor, and air. The terminal electrodes (i.e., the copper layer formed by the copper paste) are formed on the two opposite sides of the capacitor chip;

[0156] (5) The end electrodes are electroplated to complete the preparation of the external electrodes.

[0157] Performance Test:

[0158] According to the test items and test methods described in Table 4 below, the edge cracking, density, glass overflow and reliability performance of the terminal electrodes of the chip-type multilayer ceramic capacitors made of the copper paste in Examples 1 to 22 and Comparative Examples 1 to 11 were tested respectively. The specific test results are shown in Table 5 below.

[0159] Table 4 Test items, test methods and qualification standards

[0160]

[0161] Table 5 Performance test results of Examples 1 to 22 and Comparative Examples 1 to 11

[0162]

[0163]

[0164] In summary, when the copper paste in Examples 1 to 22 is applied to the terminal electrodes of chip-type multilayer ceramic capacitors, the terminal electrodes can have the following properties at the same time: the edge cracking ratio does not exceed 0.9% (the number of test samples is 1000), the density (i.e. the proportion of non-dense holes in the terminal electrode cross section to the terminal electrode cross section) does not exceed 9%, the glass overflow ratio is 0%, and the reliability (i.e. the failure ratio) does not exceed 1.5%.

[0165] Compared with Example 7, the content of coated copper powder in Comparative Example 1 is too little, so the edge cracking ratio, density, glass overflow and reliability of the terminal electrode made from the copper paste in Comparative Example 1 are not up to standard; the content of coated copper powder in Comparative Example 2 is too much, so the edge cracking ratio, density and reliability of the terminal electrode made from the copper paste in Comparative Example 2 are not up to standard; the particle size of the coated copper powder and copper powder used in Comparative Example 3 is too large, and the edge cracking ratio, density and reliability of the terminal electrode made therefrom are not up to standard; the particle size of the coated copper powder used in Comparative Example 4 is too small, and the edge cracking ratio, density, glass overflow ratio and reliability of the terminal electrode made therefrom are not up to standard; the gold content of the coated copper powder in Comparative Example 5 is too high, so the edge cracking ratio, density, glass overflow ratio and reliability of the terminal electrode made therefrom are not up to standard. The thickness of the metal oxide layer is too thin, and the edge cracking ratio, density, glass overflow ratio and reliability of the terminal electrode made therefrom are not up to the standards; the thickness of the metal oxide layer of the coated copper powder in Example 6 is too thick, and the edge cracking ratio, density and reliability of the terminal electrode made therefrom are not up to the standards; Comparative Example 7 does not use coated copper powder, and the edge cracking ratio, density, reliability and glass overflow ratio are not up to the standards; the tin oxide content in the coated copper powder in Comparative Examples 8 and 9 is too low, and the edge cracking ratio, density, reliability and glass overflow ratio are not up to the standards; the coated copper powders in Comparative Examples 10 to 11 do not contain tin oxide, and the edge cracking ratio, density, reliability and glass overflow ratio are not up to the standards.

[0166] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A copper paste, characterized in that: The invention comprises the following components in percentage by mass: 55-77.5% of copper-containing material, 7-14% of glass powder, 5-10% of binder, 0.5-3% of thixotropic agent, and 10-18% of solvent; The copper-containing material comprises 5-20% by mass of coated copper powder and 80-95% by mass of copper powder; the coated copper powder is a core-shell structure; the core of the coated copper powder is copper; the outer shell of the coated copper powder is a metal oxide layer; The metal oxide layer contains tin oxide; Taking the total mass percentage of the metal oxide layer as 100%, the mass percentage of tin oxide is 65-100%.

2. The copper paste according to claim 1, characterized in that: The metal oxide layer further contains at least one of silver oxide and nickel oxide.

3. The copper paste according to claim 1, characterized in that: The copper powder is copper flakes with an aspect ratio of 2 to 10; and / or, the average particle size of the coated copper powder is 1 to 3 μm; And / or, the average particle size of the copper powder is 2 to 4 μm; And / or, the thickness of the metal oxide layer is 50-200 nm.

4. The copper paste according to claim 1, characterized in that: The copper paste comprises the following components in percentage by mass: 63.5-70% copper-containing material, 8-12% glass powder, 6-9% binder, 1-2% thixotropic agent, and 13-15% solvent; And / or, the copper-containing material includes 8-16% by mass of coated copper powder and 84-92% by mass of copper powder.

5. The copper paste according to any one of claims 1 to 4, characterized in that: The glass powder includes the following components in percentage by mass: 40-70% BaO, 5-15% Al2O3, 10-30% B2O3, 3-10% SiO2, 3-8% CaO, 1-5% TiO2, 0-3% Na2O, and 0-3% SrO.

6. The copper paste according to claim 2, characterized in that: When the metal oxide layer is tin oxide, the coated copper powder is prepared by a preparation method comprising the following steps: The copper powder, stannous salt and organic solvent are mixed and then subjected to hydrolysis reaction with water to obtain the product; or, When the metal oxide layer is a mixture of tin oxide and nickel oxide, the coated copper powder is prepared by a preparation method comprising the following steps: A1: copper powder, stannous salt and organic solvent are mixed, and then hydrolyzed with water to obtain tin oxide coated copper powder; A2: The tin oxide coated copper powder, nickel salt and hydrazine are reacted in an alkaline environment to obtain; or, When the metal oxide layer is a mixture of tin oxide and silver oxide, the coated copper powder is prepared by a preparation method comprising the following steps: B1: copper powder, stannous salt and organic solvent are mixed, and then hydrolyzed with water to obtain tin oxide coated copper powder; B2: heating the tin oxide coated copper powder, hydrazine hydrate and alkali to react to obtain treated tin oxide coated copper powder; B3: The treated tin oxide coated copper powder is subjected to chemical silver plating, then reacted with vitamin C, and then reacted with acid and a silane coupling agent to obtain the product.

7. The method for preparing the copper paste according to any one of claims 1 to 6, characterized in that: The following steps are involved: The raw materials are mixed and then rolled to obtain the copper slurry.

8. The preparation method according to claim 7, characterized in that: The rolling step has at least one of the following characteristics: (a) The gap between the rolling mill rollers is 50-500 μm; (b) The frequency of the rolling mill roller is 20-60 r / min; (c) The number of rolling times is 4 to 8 times.

9. A chip-type multilayer ceramic capacitor, comprising terminal electrodes; characterized in that: The terminal electrode is made of the copper paste described in any one of claims 1 to 6.

10. Use of the copper paste according to any one of claims 1 to 6 in the field of electronic devices.